PENGARUH RETURN ON ASSETS, LEVERAGE, KOMPOSISI KOMISARIS INDEPENDEN, KOMITE AUDIT, DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2013-2015) - Atik Widarti, 12.05.52.0125; Maryono, Maryono (Students Journal of Accounting and Banking, 2017)
The purpose of this study was to analyze the influence of ROA, leverage, the composition of independent directors, audit committee and the size of the company against tax avoidance in companies listed on the Stock Exchange Year 2013-2015. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange in the period 2013- 2015. The sample in this study as many as 166 observation data. The sampling technique used purposive sampling. The analysis tool used is multiple linear regression. The results of the analysis can be concluded that: Profitability significant negative effect on tax avoidance. Leverage a significant negative effect on tax avoidance. BOC Independent positive and significant impact on tax avoidance.The audit committee and no significant negative effect on tax avoidance.Company size and no significant negative effect on tax avoidance.Keywords: ROA, Leverage, The Composition of Independent Directors, Audit Committee, The Size of The Company and Tax Avoidance